2014
DOI: 10.1002/ajmg.a.36698
|View full text |Cite
|
Sign up to set email alerts
|

Genetic testing and corresponding services among individuals with autism spectrum disorder (ASD)

Abstract: The purpose of this study was to assess use of genetic testing and corresponding genetic services for children with Autism Spectrum Disorder (ASD). Survey data from 397 parents of individuals with ASD was collected using the Center for Autism and Related Disabilities client registry. Participants reported that 41.2% of the individuals with ASD had undergone any type of genetic testing. However, only 21.3% of individuals with ASD had been referred to a genetics specialist. Diagnosis and level of functioning wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 23 publications
4
29
0
Order By: Relevance
“…The intention of parents within our study to have their children receive testing was found relatively high at 84.3%, which suggests that majority of participants are likely to consider having their ASD-affected child undergo CMA. This number is consistent with existing findings about the level of parent interest toward ASD genetic testing [12,13,21,22,42]. For instance, Vande Wydeven et al [24] found parental interest in utilizing genetic services at 90%.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The intention of parents within our study to have their children receive testing was found relatively high at 84.3%, which suggests that majority of participants are likely to consider having their ASD-affected child undergo CMA. This number is consistent with existing findings about the level of parent interest toward ASD genetic testing [12,13,21,22,42]. For instance, Vande Wydeven et al [24] found parental interest in utilizing genetic services at 90%.…”
Section: Discussionsupporting
confidence: 88%
“…Concerning the levels of parent interest, studies have consistently found that supportive attitudes to pursue genetic testing are high [19][20][21][22]. Despite positive perceptions as well as the potentially beneficial outcomes of a genetic diagnosis, actual utilization of CMA among other genetic testing options are reported as being low among parents of children with ASD [13,[22][23][24][25].…”
Section: Doi: 107243/2054-992x-4-4mentioning
confidence: 99%
See 1 more Smart Citation
“…This has also been observed in a study carried out in USA, which showed that genetic testing was often ordered in the absence of the accompanying genetic services (Cuccaro et al 2014). Genetic tests that scan the whole genome, such as CMA or exome analysis, involve a significant amount of complexity and may identify incidental findings, variants of unknown significance and variants of variable expression and incomplete penetrance.…”
Section: Discussionmentioning
confidence: 76%
“…A study carried out in USA in 2009 reported that only 24% of parents whose child was diagnosed with ASD had seen a genetic counselor (Selkirk et al 2009). More recent studies based also in USA reported similar rates of utilization of genetic services by families of ASD patients, ranging from 20-28% (Amiet et al 2014;Chen et al 2013;Cuccaro et al 2014;Vande Wydeven et al 2012). It was hypothesized that the low utilization rate was mostly due to a lack of referral, possibly related to an extended unawareness of the clinical utility of genetics for ASD among other professionals (Salm et al 2014).…”
Section: Discussionmentioning
confidence: 97%